Post Office, Dawson, Yukon Territory, approximately 1899. - Hegg, Eric A., 1867-1948 (1899)
Shows crowd of people standing in front of and on the balcony of the post office. Caption on image: "Post Office, Dawson, N.W.T." Original image in Hegg Album 22, page 27.